The impact of the pandemic highlights the urgent need for myopia guidelines: the clinicians’ role : editorial - Németh, János; Aclimandos, Wagih A; Tapasztó, Beáta; Jonas, Jost B.; Grzybowski, Andrzej; Nagy, Zoltán Zsolt (European journal of ophthalmology, 2023)
Myopia is already one of the leading causes of permanent vision impairment, including blindness, and the COVID-19 pandemic has exacerbated the global myopia-related burden among children owing to home confinement, increased screen time (e-learning), and decreased outside activities. To reverse the rising trend of myopia and myopia-related blindness, collaborative efforts are required. There is a wealth of evidence-based medicine (EBM) data on the epidemiology of myopia and effective interventions, but very little has been published on the clinicians’ roles and responsibilities. However, this aspect is critical because preventing the onset and progression of myopia necessitates extensive health promotion and advocacy efforts among decision-makers. Only broad medical expert collaboration can bring about the necessary changes in children's lifestyle and education. This article discusses clinicians’ critical roles in preventing the onset and progression of myopia.
Erstmals veröffentlicht: 29. November 2022
Gesehen am 17.09.2024